2018
DOI: 10.1371/journal.pone.0195430
|View full text |Cite
|
Sign up to set email alerts
|

The impact of attachment distress on affect-centered mentalization: An experimental study in psychosomatic patients and healthy adults

Abstract: IntroductionWe investigated the impact of attachment distress on affect-centered mentalization in a clinical and a non-clinical sample, comparing mentalization in a baseline condition to mentalization under a condition of attachment distress.MethodsThe sample consisted of 127 adults who underwent inpatient psychosomatic treatment, and 34 mentally healthy adults. Affect-centered mentalization was assessed by analyzing participants’ narratives on interpersonal situations in a baseline condition with the Levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 83 publications
1
3
0
Order By: Relevance
“…Consistent with our hypothesis, the increase of NE could be a risk factor that leads to automatic MSI modes in stressful contexts, which manifest as fast but inaccuracy-prone attributions of others. This finding is consistent with earlier studies that indicate the effect of threat induction on mentalizing (Beyer et al, 2013;Górska, 2018;Herrmann et al, 2018;Nolte et al, 2013). Further, we found that individual differences manifest only when a situation is personal and emotional, in terms of attachment needs, and demands for affect regulation abilities.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our hypothesis, the increase of NE could be a risk factor that leads to automatic MSI modes in stressful contexts, which manifest as fast but inaccuracy-prone attributions of others. This finding is consistent with earlier studies that indicate the effect of threat induction on mentalizing (Beyer et al, 2013;Górska, 2018;Herrmann et al, 2018;Nolte et al, 2013). Further, we found that individual differences manifest only when a situation is personal and emotional, in terms of attachment needs, and demands for affect regulation abilities.…”
Section: Discussionsupporting
confidence: 93%
“…A recent cohort study with magnetic resonance imaging (Tozzi et al, 2020) confirmed that the severity and type of childhood maltreatment influence brain maturation, particularly in regions involved in mentalization abilities. A negative association between childhood maltreatment and mentalization is supported by studies in children (Ensink et al, 2017; Tessier et al, 2016) and adolescents (Quek et al, 2017), although studies on clinical samples are still inconsistent (Brüne et al, 2016; Chiesa and Fonagy, 2014; Herrmann et al, 2018; Weijers et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, hikikomori life stories are characterized by traumatic experiences concerning separation and loss of significant others and by psychosomatic complaints involving body image distress since childhood and early adolescence. Given the impact of attachment distress on affect-centered mentalization and the relevance of the frustrating experiences of loss and separation for the onset of psychosomatic symptoms (Herrmann et al, 2018), a failed mourning process due to an unresolved loss can be hypothesized. Within a psychosomatic frame (Aisenstein & Rappoport de Aisemberg, 2010), the potential reduced mentalization of loss/separation episodes reported by participants (e.g., romantic relationship breakup, significant others' death, or loved ones' illness) may have generated a form of death anxiety, which is avoided by repressing aggressive impulses and projecting narcissistic libido onto the body, thus resulting in psychosomatic distress.…”
Section: Discussionmentioning
confidence: 99%